2004
DOI: 10.1097/01.rlu.0000129121.55248.f5
|View full text |Cite
|
Sign up to set email alerts
|

Retroperitoneal Malignant Peripheral Nerve Sheath Tumor: Evaluation With Serial FDG-PET

Abstract: Retroperitoneal malignant peripheral nerve sheath tumor (MPNST), a rare type of neurogenic tumor, was diagnosed in a 14-year-old girl with a history of neurofibromatosis type 1 (NF1). Immunochemistry demonstrated spindle cells positive for S-100 protein. The patient had multiple tumor recurrences and she was evaluated with serial F-18 fluorodeoxyglucose (FDG) positron emission tomography (PET). A tumor in the right iliac wing showed increased FDG uptake on PET. FDG-PET played an important role in therapy plann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…[ 9 ] It thus plays an important role in the staging, restaging and post-therapy follow-up of MPNST in NF1. [ 10 ] A high FDG uptake has been documented in sporadic MPNSTs also, as is well seen in the coronal maximum intensity projection image [ Figure 2 ] in the present case.…”
Section: Case Reportsupporting
confidence: 81%
“…[ 9 ] It thus plays an important role in the staging, restaging and post-therapy follow-up of MPNST in NF1. [ 10 ] A high FDG uptake has been documented in sporadic MPNSTs also, as is well seen in the coronal maximum intensity projection image [ Figure 2 ] in the present case.…”
Section: Case Reportsupporting
confidence: 81%
“…For example, Cardona et al [43] reported 100% sensitivity and 83% specificity in a population of 25 patients (of whom five had NF1) with an absolute SUV max cut-off value for malignancy of 1.8. But other recent studies have demonstrated that an absolute SUV max >3 is associated with poor prognosis and is correlated with Ki67 levels [41], [42], [44]; Tsai [45] set the SUV max malignancy threshold at 4. Karabatsou also reached a 4 SUV max cut-off, but this was in a very small set of 9 patients [46].…”
Section: Discussionmentioning
confidence: 99%
“…Similar imaging findings in the vertebral column on PET/CT should consider the possibility of lymphoma, 6,7 chordoma, 8 metastasis, 9 epithelioid hemangioma, 10 tenosynovial giant cell tumor, 11 myeloma, 12 and Rosai-Dorfman disease 13 . This case highlights that solitary lytic thoracic vertebral lesion with intense FDG uptake should regard MPNST as a differential diagnosis and that FDG PET/CT has an important role in the initial staging of MPNST 14–16 …”
mentioning
confidence: 73%
“…13 This case highlights that solitary lytic thoracic vertebral lesion with intense FDG uptake should regard MPNST as a differential diagnosis and that FDG PET/CT has an important role in the initial staging of MPNST. [14][15][16]…”
Section: Figurementioning
confidence: 99%